Georg e Santayana: life and doctrine - Wagner Grau, Patrick (2009)
This text gives an approach to George Santayana`s though his literary and philosophical work, and also through the conditionings of his personal life and the influences of notable writers and philosophers that led him through naturalistic and strongly positivistic philosophy